2020
DOI: 10.1124/jpet.120.000121
|View full text |Cite
|
Sign up to set email alerts
|

KATP Channel Openers Inhibit Lymphatic Contractions and Lymph Flow as a Possible Mechanism of Peripheral Edema

Abstract: Pharmacological openers of adenosine triphosphate-sensitive K + (K ATP) channels are effective antihypertensive agents, but off-target effects, including severe peripheral edema limit their clinical usefulness. It is presumed that the arterial dilation induced by K ATP channel openers (KCOs) increases capillary pressure to promote filtration edema. However, K ATP channels also are expressed by lymphatic muscle cells (LMCs), raising the possibility that KCOs also attenuate lymph flow to increase interstitial fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The resuspension step was repeated twice to eliminate residual enzymes from the cell suspension solution. Previous studies by us have shown that this method of LMC isolation produces individual cells for analysis (Garner et al, 2021).…”
Section: Flow Cytometrymentioning
confidence: 90%
See 1 more Smart Citation
“…The resuspension step was repeated twice to eliminate residual enzymes from the cell suspension solution. Previous studies by us have shown that this method of LMC isolation produces individual cells for analysis (Garner et al, 2021).…”
Section: Flow Cytometrymentioning
confidence: 90%
“…Lymph flow was recorded continuously prior to and during the 20 min incubation period with DANT and for 60 min after rapid infusion of DOX. Customized software tracked individual lymph cells in flow as described in detail earlier by us (Sarimollaoglu et al, 2018;Stolarz et al, 2019;Garner et al, 2021). Using these data files, flow velocity and positive volumetric flow were calculated to evaluate the effects of DOX and DANT on lymph flow in vivo.…”
Section: High-speed In Vivo Microscopymentioning
confidence: 99%
“…Glibenclamide -induced block of these channels reportedly depolarizes guinea pig lymph muscle cells but has little to no effect on contractions of isolated rat mesenteric lymph vessels and isolated human thoracic ducts (Mizuno et al, 1999;Mathias and von der Weid, 2013;Telinius et al, 2014b). Although K ATP channels may be inactive under some conditions, they can cause hyperpolarization, inhibition of rhythmic contractions, and loss of lymph flow when activated by pharmacological agents or gain-of-function mutations (Mathias and von der Weid, 2013;Davis et al, 2020;Garner et al, 2021).…”
Section: Lymphatic Muscle Cell Physiology and Excitabilitymentioning
confidence: 99%
“…In LMCs, as with most smooth muscle, K + permeability is critical for resting membrane potential regulation ( Ohhashi and Azuma, 1982 ; Telinius et al, 2014a ) that governs the muscle excitability and contractile activity. Hyperpolarization by elevated K + conductance can either overwhelm the depolarizing influence of inwards currents, such as those provided by Ano1, to prevent or slow the depolarization to the critical threshold, or with excessive K + currents hyperpolarize the membrane out of the voltage window permissive for rhythmic oscillations ( Mizuno et al, 1999 ; Mathias and von der Weid, 2013 ; Davis et al, 2020 ; Garner et al, 2021 ; Kim et al, 2021 ). Four different classes of K + channels have been identified in LMCs: Ca 2+ -activated K + channels, volage-dependent K + changes, ATP-sensitive K channels (K ATP ), and inward rectifier K + .…”
Section: Introductionmentioning
confidence: 99%
“…K ATP channels appear to be partially or transiently active under the resting condition in lymphatic vessels as glibenclamide (FDA-approved K ATP antagonist) increases the lymphatic contractile frequency in the human thoracic duct ( Telinius et al, 2014a ; Davis et al, 2020 ). Open K ATP channels prevent action potential generation in lymphatic vessels resulting in phasic contraction cessation, and clinically relevant concentrations of K ATP channel may impair in vivo lymphatic contractile function ( Garner et al, 2021 ). A relatively small alteration of resting membrane potential (e.g., 4mV) through K ATP modulation is enough to initiate lymphatic phasic contraction from quiescent vessels ( Telinius et al, 2014a ) or cease electrical and contractile activity ( Davis et al, 2020 ), indicating the powerful role of K ATP as a mediator lymphatic contractile dysfunction.…”
Section: Introductionmentioning
confidence: 99%